Long-term Impact of Weight Loss Intervention on Changes in Cognitive Function: Exploratory Analyses from the Action for Health in Diabetes Randomized Controlled Clinical Trial. (25th August 2017) - Espeland, Mark A; Carmichael, Owen; Hayden, Kathleen; Neiberg, Rebecca H; Newman, Anne B; Keller, Jeffery N; Wadden, Thomas A; Rapp, Stephen R; Hill, James O; Horton, Edward S; Johnson, Karen C; Wagenknecht, Lynne; et al.
Abstract: Background: Diabetes adversely impacts cognition. Lifestyle change can improve diabetes control and potentially improve cognition. We examined whether weight loss through reduced caloric intake and increased physical activity was associated with slower cognitive aging in older adults with type 2 diabetes mellitus. Methods: The Look AHEAD randomized controlled clinical trial delivered 10 years of intensive lifestyle intervention (ILI) that yielded long-term weight losses. During 5 years spanning the end of intervention and postintervention follow-up, repeated cognitive assessments were obtained in 1, 091 individuals who had been assigned to ILI or a control condition of diabetes support and education (DSE). We compared the means and slopes of scores on cognitive testing over these repeated assessments. Results: Compared with DSE, assignment to ILI was associated with a −0.082 SD deficit in mean global cognitive function across repeated assessments ( p = .010). However, overweight (body mass index [BMI] < 30 kg/m 2 ) ILI participants had 0.099 (95% confidence interval [CI]: −0.006, 0.259) better mean global cognitive function compared with overweight DSE participants, while obese (BMI ≥ 30 kg/m 2 ) ILI participants had −0.117 (−0.185, −0.049) SD worse mean composite cognitive function scores (interaction p = .014) compared to obese DSE participants. For both overweight and obese participants, cognitive decline was marginally (−0.014 SD /y overall) steeper for ILI participants ( p = .068), with 95% CI for differences in slopes excluding 0 for measures of attention and memory. Conclusions: The behavioral weight loss intervention was associated with small relative deficits in cognitive function among individuals who were obese and marginally greater cognitive decline overall compared to control. ClinicalTrials.gov Identifier: NCT00017953